Influence of Remelting Treatment on Corrosion Behavior of Amorphous Alloys. Issue 2 (February 2017) - Jingtao, Liu; Jixin, Hou; Xiaorong, Zhang; Jing, Guo; Lingfeng, Xu; Guiju, Fan
Abstract: The corrosion behavior of Gd56 Al26 Co18 and Sm56 Al26 Co18 amorphous alloys in 0.01 mol/L NaOH solution has been researched by polarization curves, EIS technique, XRD and SEM. The free volume was also investigated by DSC technique. We find that the corrosion resistance of amorphous alloys in 0.01 mol/L NaOH solution increases after remelting. The corrosion resistance of Gd-based amorphous ribbons is better than that of the Sm-based amorphous ribbons in 0.01 mol/L NaOH solution. In addition, the amount of free volume of remelting amorphous ribbons is less than that of first-time melting amorphous ribbons.